Static cerebrovascular pressure autoregulation remains intact during deep hypothermia. Issue 9 (18th July 2017) - Goswami, Dheeraj; McLeod, Katherine; Leonard, Samantha; Kibler, Kathleen; Easley, Ronald Blaine; Fraser, Charles D.; Andropoulos, Dean; Brady, Ken
Summary: Background: Clinical studies measuring cerebral blood flow in infants during deep hypothermia have demonstrated diminished cerebrovascular pressure autoregulation. The coexistence of hypotension in these cohorts confounds the conclusion that deep hypothermia impairs cerebrovascular pressure autoregulation. Aim: We sought to compare the lower limit of autoregulation and the static rate of autoregulation between normothermic and hypothermic piglets. Methods: Twenty anesthetized neonatal piglets (5‐7 days old; 10 normothermic and 10 hypothermic to 20°C) had continuous measurements of cortical red cell flux using laser Doppler flowmetry, while hemorrhagic hypotension was induced without cardiopulmonary bypass. Lower limit of autoregulation was determined for each subject using piecewise regression and SRoR was determined above and below each lower limit of autoregulation as (%change cerebrovascular resistance/%change cerebral perfusion pressure). Results: The estimated difference in lower limit of autoregulation was 1.4 mm Hg (lower in the hypothermic piglets; 95% C.I. −10 to 14 mm Hg; P =0.6). The median lower limit of autoregulation in the normothermic group was 39 mm Hg [IQR 38‐51] vs 35 mm Hg [31‐50] in the hypothermic group. Intact steady‐state pressure autoregulation was defined as static rate of autoregulation >0.5 and was demonstrated in all normothermic subjects (static rate of autoregulation=0.72 [0.65‐0.87]) and in 9/10 of the hypothermic subjects (static rate of autoregulation=0.65 [0.52‐0.87]). This difference in static rate of autoregulation of 0.06 (95% C.I. −0.3 to 0.1) was not significant ( P =0.4). Conclusion: Intact steady‐state cerebrovascular pressure autoregulation is demonstrated in a swine model of profound hypothermia. Lower limit of autoregulation and static rate of autoregulation were similar in hypothermic and normothermic subjects.